An Innovative Surgical Technique: Dorsal SMAS Periosteal Flap for Nasal Radix Augmentation - Springford, Laurie R.; Alhasan, Mohamad Sami (Facial Plastic Surgery, 2024)
The nasal radix holds significant importance in facial aesthetics, sometimes requiring augmentation to create balanced facial profiles. A flat nasal radix can cause inadequate projection and the appearance of a pseudo-hump. In these cases, rhinoplasty surgeons should avoid working on the pseudo-hump and focus on elevating the radix to achieve the desired aesthetic outcome. Here, we introduce a novel approach and “how we do” the dorsal superficial musculoaponeurotic system (SMAS) periosteal flap for nasal radix augmentation. Using an external septorhinoplasty approach, the initial dissection is performed over the nasal bones in the supra-SMAS plane. Then, an SMAS flap is designed with two lateral and one caudal incision extending to the osseocartilaginous junction and dissected subperiosteally. Next, the flap is rotated to fill the space between the nasal bones and skin, augmenting the nasal radix. Compared to traditional methods, this approach always utilizes the patient's own tissue, minimizes rejection, and ensures seamless integration, providing lasting results. It ensures structural stability and avoids the use of cartilage, eliminating the risk of resorption. The dorsal SMAS periosteal flap presents a tailored, durable solution that consistently yields excellent outcomes while overcoming the risk of instability associated with cartilage grafts.
Keywords: septorhinoplasty; rhinoplasty; external septorhinoplasty; nasal radix augmentation